Pengaruh Citra Merek dan Trust terhadap Minat Beli di Marketplace Shopee (Studi pada Masyarakat Pesisir Suku Bajo di Kabupaten Bombana) - Almansyah Rundu Wonua; Ismanto Ismanto; Santi Santi (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This research aims to determine: (1) The influence of brand image on purchase interest at the Shopee marketplace in the coastal communities of the Bajo tribe in Kab. Bombana. (2) The Influence of Trust on Purchase Interest in the Shopee Marketplace in the Bajo Tribe Coastal Community in Kab. Bombana. (3) The Influence of Brand Image on Trust in the Shopee Marketplace in the Bajo Tribe Coastal Community in Kab. Bombana. And (4) The Effect of Trust Mediation on Brand Image and Purchase Interest at the Shopee Marketplace in the Bajo Tribe Coastal Community in Kab. Bombana This research is an explanatory research model with a quantitative approach. Data collection in this research used documentation and distribution of questionnaires. The population of this research is the entire Bajo Tribe Coastal Community in Kab. Bombana. Meanwhile, the sample for this research was 140 respondents using the sampling technique used in this research using purposive sampling technique, which is a technique for determining samples with certain considerations. Research instrument testing uses validity and reliability tests with SPSS 22.0. The data analysis technique used in this research is Structural Equation Modeling (SEM) based on Analysis of Moments of Structures (AMOS) with Normality testing, outliers and testing the Goodness of fit index (GFI) structural model with AMOS 24.0. Based on the research results, it is known that there is a positive and significant influence between the Brand Image variable on Purchase Interest, this is shown by the P-Value value of 0.041. The Trust variable has a positive and significant effect on Purchase Interest, this is shown by the P-Value value of 0.014. The Brand Image variable has a positive and significant effect on Trust, this is shown by the P-Value value of 0.000. And the Trust variable mediates brand image on positive buying interest but is not significant as shown by the P-Value value of 0.138.